Fatostatin Inhibits Cancer Cell Proliferation by Affecting Mitotic Microtubule Spindle Assembly and Cell Division - Gholkar, Ankur A.; Cheung, Keith; Williams, Kevin J.; Lo, Yu-Chen; Hamideh, Shadia A.; Nnebe, Chelsea; Khuu, Cindy; Bensinger, Steven J.; Torres, Jorge Z. (The Journal of biological chemistry, 2016)
The sterol regulatory element-binding protein (SREBP) transcription factors have become attractive targets for pharmacological inhibition in the treatment of metabolic diseases and cancer. SREBPs are critical for the production and metabolism of lipids and cholesterol, which are essential for cellular homeostasis and cell proliferation. Fatostatin was recently discovered as a specific inhibitor of SREBP cleavage-activating protein (SCAP), which is required for SREBP activation. Fatostatin possesses antitumor properties including the inhibition of cancer cell proliferation, invasion, and migration, and it arrests cancer cells in G2/M phase. Although Fatostatin has been viewed as an antitumor agent due to its inhibition of SREBP and its effect on lipid metabolism, we show that Fatostatin's anticancer properties can also be attributed to its inhibition of cell division. We analyzed the effect of SREBP activity inhibitors including Fatostatin, PF-429242, and Betulin on the cell cycle and determined that only Fatostatin possessed antimitotic properties. Fatostatin inhibited tubulin polymerization, arrested cells in mitosis, activated the spindle assembly checkpoint, and triggered mitotic catastrophe and reduced cell viability. Thus Fatostatin's ability to inhibit SREBP activity and cell division could prove beneficial in treating aggressive types of cancers such as glioblastomas that have elevated lipid metabolism and fast proliferation rates and often develop resistance to current anticancer therapies.